2011
DOI: 10.1111/j.1439-0396.2010.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary addition of Macleaya cordata alkaloid extract on growth performance, caecal indices and breast meat fatty acids profile in male broilers

Abstract: The aim of this experiment was to investigate whether a low-dietary application (15 mg/kg) of an alkaloid preparation containing quaternary benzo[c]phenanthridine alkaloids and obtained from Macleaya cordata (Sangrovit) influenced caecal metabolism, growth performance and long-chain fatty acid composition of breast meat. One-day-old broiler chicks (Cobb 500) were fed a diet without supplement or with a 15 mg/kg dose of Sangrovit (C and A groups respectively) for 5 weeks. Although the A treatment was not accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 23 publications
2
37
1
Order By: Relevance
“…Other studies have evaluated the effects of MCEP inclusion into poultry feed. MCEP fed to male chickens for fattening for five weeks at 15 mg/kg feed decreased β-glucuronidase and β-glucosidase caecal activities, while increasing production of certain caecal short chain fatty acids [2]. Other research found that feeding MCEP to chickens for fattening at 20 mg/kg feed may optimize nutrient absorption by reducing excessive caecal fermentation pathways without increasing the pH of the caecal contents or diminishing glycolytic activity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have evaluated the effects of MCEP inclusion into poultry feed. MCEP fed to male chickens for fattening for five weeks at 15 mg/kg feed decreased β-glucuronidase and β-glucosidase caecal activities, while increasing production of certain caecal short chain fatty acids [2]. Other research found that feeding MCEP to chickens for fattening at 20 mg/kg feed may optimize nutrient absorption by reducing excessive caecal fermentation pathways without increasing the pH of the caecal contents or diminishing glycolytic activity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Both of them have been used more and more wildly not only in human medicinal areas, but also in the stockbreeding and agriculture. The M. cordata extract is an exemplification that made of injection which has antibacterial and antipyretic effect of pigs, chickens and fish [3], [4], [6], [8]. We have also developed a new Chinese herbal medicinal veterinary drugs based on the M. cordata extract, which is already in the category II new Chinese herbal medicinal veterinary drugs in China (2011 Novel Veterinary Drugs Certificate NO.…”
Section: Discussionmentioning
confidence: 99%
“…Many benzylisoquinoline alkaloids (BIAs), including sanguinarine (SA), chelerythrine (CHE), protopine (PRO), allocryptopine (ALL), dihydrochelerythrine (DHCHE) and dihydrosanguinarine (DHSA) were extracted from Macleaya spp. Pharmaceutical researches showed that these alkaloids were its major bio-active components [4], [5], [6], [7]. Recently, it has been found that SA and CHE had antiseptic and antitumor activities [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic activity was expressed as μmol product formed per hour per gram of digesta. The above procedure concerns the extracellular activities of bacterial enzymes released from bacterial cells into the gastrointestinal environment (Juskiewicz et al, 2011). To determine the total enzymatic activity of selected bacterial enzymes in the caecal sample, which includes extracellular and intracellular activities of bacterial enzymes, the caecal sample diluted in phosphate buffer (as described above) was mechanically disrupted by vortexing with glass beads (212-300 μm diameter; four periods of 1 min with intervals of 1 min on ice).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Ammonia was determined by microdiffusion analysis in Conway's dishes (Hofirek and Haas, 2001) and SCFAs were analysed using a gas chromatograph (Shimadzu GC-2010, Kyoto, Japan) equipped with a capillary column (SGE BP21, 30 m × 0.53 mm, SGE Europe Ltd., Kiln Farm Milton Keynes, UK) as described earlier (Juskiewicz et al, 2011). The activity of bacterial enzymes (α-and β-glucosidase, α-and β-galactosidase, β-glucuronidase, α-arabinopyranosidase, β-xylosidase) released into the caecal environment was measured by the rate of p-or o-nitrophenol release from their nitrophenylglucosides.…”
Section: Chemical Analysismentioning
confidence: 99%